The Dark Side of Photocatalysis: One Thousand Ways to Close the Cycle. Issue 19 (31st March 2020) - Capaldo, Luca; Ravelli, Davide
Abstract : Photocatalytic strategies have recently revolutionized the field of organic synthesis. However, while the progress has been impressive in terms of reported methodologies, less attention has been devoted to mechanistic aspects. In this regard, key to the development of efficient strategies is the recovery of the exhausted photocatalyst formed upon quenching of the excited state. This review summarizes the different ways available to turn over the photocatalyst and classifies them according to the species responsible for this step, being a reaction intermediate, a co‐catalyst, a reaction partner or an electrode. Finally, an analysis of the common aspects of the described alternatives is offered, also showcasing how the tuning of the photocatalyst turn‐over step can completely divert the reaction outcome. Abstract : An unprecedented perspective on photocatalytic processes is offered, with a focus on the way photocatalytic cycles are turned over. The given examples are classified according to the species responsible for photocatalyst restoration, namely: a reaction intermediate, a co‐catalyst, a reaction partner, an electrode, etc. It is demonstrated why the photocatalyst recovery is pivotal to devise an efficient synthetic protocol, showcasing how a fine tuning of this step can completely divert the reaction outcome.